Analisis Penerapan Sila Kemanusiaan yang Adil dan Beradab dalam Mengatasi Isu Kesenjangan Sosial Ekonomi Dunia Pendidikan pada Masyarakat Perkotaan Modern - Benediktus Josua Gea; Despri Mariyani Siahaan; Rupma Riana Saragih; Susi Krisdayanti Marbun; Yohana Sinurat; Ramsul Nababan (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The purpose of this study is to explore the application of just and civilized humanitarian principles in an effort to address the problem of socioeconomic disparities in modern urban societies. Socioeconomic disparities are an important issue that impacts people's access to education and other social services. The study identified various factors that cause imbalances in the distribution of resources, especially in the education sector, which in turn leads to increasingly stark social and economic disparities. Using a qualitative approach and descriptive methods, this study collects data from various sources such as journals, articles, and public policy. The results of the analysis show that the application of Pancasila values, especially the principles of just and civilized humanity, has a significant role in creating social justice and economic equity. From the results of the study, it is concluded that the application of fair and civilized humanitarian principles in education and social policies needs to be improved so that every individual has equal opportunities to access education. This study recommends strategies that include collaboration between sectors and increased understanding of Pancasila values to encourage a sense of collective responsibility in society. With these measures, it is hoped that they can reduce socioeconomic disparities and realize common prosperity.